ANALISIS BEBAN PENGGUNA PADA TELETRAFIK INTERNET STTA MENGGUNAKAN SISTEM SHARING - Putri, Amanda Cahya Ristia; Astuti, Yenni (SENATIK STT Adisutjipto, 2017)
Internet needs in education has become a basic requirement, whether it is for faculty, students, complementary components of universities such as bureaus, public relations, TU, and non-academic staff. As the number of Internet users continues to increase, especially in educational institutions, including STTA’s, an observation of the STTA Internet network data stream is conducted. A parameter to be observed is user's load, as it affects the quality of services that will be generated by the STTA Internet Network.This research provides an analysis to measure the size of user load as well as to know the amount of loss so that it can be a reference in subsequent research to reduce the amount of loss in order to fit in the good category traffic. Model sharing system is used to describe traffic data both elastic and stream at flow level.Observation results show that the average arrival rate of STTA is 11 kbps with average service rate of 59 kbps. This research uses the measured throughput of 86 Mbps. Throughput is calculated from the total number of bits of a successful packet arrivals per second via a network system. With the Internet link capacity of 100 Mbps STTA, after the analysis by the method of sharing system, it is seen that the traffic flow loss is 16%. From this traffic flow loss value, it can be concluded that the STTA’s Internet is include in medium category.